Ateuchus cujuchi n. sp., a new inquiline species of Scarabaeinae (Coleoptera: Scarabaeidae) from tuco-tuco burrows in Bolivia - Génier, François (Zootaxa, 2015)
In 2012, P. Skelley and J. Wappes were investigating the insect fauna of Ctenomys (Blainville, 1826) (Rodentia: Ctenomyidae) burrows at low elevation in Santa Cruz de la Sierra province, Bolivia. A number of beetles were extracted from this microhabitat and among them, 50 specimens belonging to the New World genus Ateuchus Weber from the subfamily Scarabaeinae (Coleoptera: Scarabaeidae). The specimens were submitted to the author for identification and did not match any currently described species. Although South American species of the genus Ateuchus are critically in need of a modern revision, it is considered important to describe this particular species as it is the first one recorded from mammal burrows in South America and it is easily distinguishable from all other known Ateuchus.